Enhanced Surface Properties of Hydroxyapatite by Grafting Tartaric Acid for Sustained Release of Moxifloxacin. Issue 14 (10th April 2019) - Zarif, Faiza; Sharif, Faiza; Batool, Madeeha; Haider, Ammar; Gul, Urooj; Gilani, Mazhar A.; Idrees, Ayesha; Tabassum, Sobia
Abstract: Grafting of material with organic functionalities helps to tune material's surface properties. Surface properties of a biomaterial play a significant role for sustained release of therapeutic agent. To evaluate the effect of tartaric acid concentration on HA surface properties and phase purity, a series of tartaric acid grafted HA (t‐HA) samples were prepared via in situ wet chemical synthesis. Grafting of HA with tartaric acid improved its surface properties. The surface area of 737 m 2 /g was gained when 0.05 mole equivalent of tartaric acid was used for HA grafting. X‐ray diffraction patterns of t‐HA samples have shown low degree of crystallinity compared to HA sample. XRD results showed the formation of calcium tartrate phase along with HA when higher concentration of tartaric acid was used for synthesis. The HA and t‐HA samples were explored for the delivery of moxifloxacin. High surface area, surface charge and low degree of crystallinity have improved electrostatic interaction between the drug and t2‐HA and help in sustained release of moxifloxacin. In vitro antibacterial activity of drug loaded samples showed activity against S. aureus. Calcium tartrate containing samples t3‐HA, t4‐HA and t5‐HA showed, however, moderate inhibition against S. aureus without drug. In vitro cell studies by using MC3T3 cell line showed that prepared HA and t‐HA samples did not exhibit any cytotoxic effect. Abstract : A series of tartaric acid grafted hydroxyapatite (t‐HA) samples were prepared via wet chemical synthesis. High surface area of 737.083 m 2 /g of t‐HA was obtained when 0.05 mol equivalent of tartaric acid was used for HA synthesis. Calcium tartrate containing samples t3‐HA, t4‐HA and t5‐HA showed antibacterial activity. Grafted HA showed slow release of moxifloxacin. Alamar Blue assay showed comparable biocompatibility of t‐HA and HA samples.